Bonding through novel solder-metallic mesh composite design. (15th December 2018) - Lis, Adrian; Tatsumi, Hiroaki; Matsuda, Tomoki; Sano, Tomokazu; Kashiba, Yoshihiro; Hirose, Akio
Abstract: Thin metallic Cu and Ni meshes were successfully embedded within SAC305 solder joints. Defects (residues) within the joint were removed by a vacuum step in the bonding sequence. The metallic mesh inlets were metallurgically bonded by the formation of scallop-like Cu6 Sn5 and faceted Ni3 Sn4 intermetallic compounds (IMCs) at the Cu mesh-SAC305 solder (CMS) and Ni mesh-SAC305 solder (NMS) interfaces, respectively. After process optimization, the averaged shear strengths were found to be 44.1 (reference), 44.7 (+1%), and 51.4 MPa (+16%) for SAC305, NMS, and CMS composite joints, respectively. The solder-substrate-mesh interaction resulted in a characteristic fracture pattern, with the cracking path partly within the solder and partly at the solder-mesh interface. Finite element (FE) simulations suggested a mesh-induced stiffening effect of the solder joint by 5%. The additional reinforcement (11%) introduced by the Cu mesh inlets was attributed to a locally enhanced fracture resistance. Graphical abstract: Highlights: Thin Cu and Ni meshes were integrated in SAC305 solder layers. The metallic meshes were bonded by the formation of intermetallic compounds. Composite joints provided shear strengths up to 16% higher. Reinforcement was achieved by stiffening and a locally increased fracture resistance.